Scientific-based learning scenario to improve student’s higher order thinking skills: A development concept - Ririn Setyowati; Sarwanto Sarwanto; Muzzazinah Muzzazinah (Prosiding Konferensi Ilmiah Dasar, 2020)
The era of the industrial revolution demands the ability of individuals to think at a high level amid technology-based civilization. Higher Order Thinking Skills are part of essential skills in the 21st century as a provision for future generations to avoid stuttering about future changes. Education becomes the most responsible field in producing quality human resources and has global competitiveness. Teachers as education implementers must realize that students' higher-order thinking skills can be developed if learning is organized in scenarios that are oriented towards active learning. Scientific-based learning scenarios can get students used to finding knowledge through experience, not from material already in the book. The concept of developing a scientific approach component that is integrated into the learning scenario aims to improve the HOTS of students. The development of the HOTS concept from four literature sources, namely concept Anderson & Krathwohl, Brookhart, Marzano, and the Assessment and Learning Center in Indonesia, is an effort to compile HOTS indicators by taking into account the strengths and weaknesses of each concept.